State Responsibility to Protecting Crypto Assets Customers - Yazid Bustomi (Universitas Negeri Semarang, 2023)
Cryptocurrency regulation presents a unique and monumental challenge for policymakers. Many countries have threatened to impose complete bans on the use and trading of cryptocurrencies. This study aims to describe the responsibility of the State in protecting crypto asset customer in Indonesia. The normative juridical research method with data sources including primary data and secondary data is used as an analytical tool. The results of the study show that in order to protect crypto asset customer in Indonesia, the government refers to the Commodity Futures Trading Law No. 10 of 2011 which can provide legal protection for investors. Hedging of commodity futures contracts is carried out under the direct supervision of the Commodity Futures Trading Regulatory Agency (BAPPEBTI).